Heat and cold therapy in sports – Rethinking mechanisms and clinical applications - Hotfiel, Thilo; Engelhardt, Martin; Hammer, Christian; Grim, Casper; Freiwald, Jürgen (Sport-Orthopädie, Sport-Traumatologie, 2024)
Injury and exercise during training and competition are associated with mechanical and metabolic stress. This results in a (patho-) physiological and immunological reaction that can have a physiological (increased endurance and performance) or pathophysiological effect (overuse, misload, misuse, injuries). In this context, heat and cold therapy are among the most traditional and established forms of physical therapy for supporting training-related adaptation reactions, optimizing regeneration, and treating sports injuries. Despite the frequency of its application, there are only a few empirically proven recommendations for its use in sports, depending on the indication and goal. This review article considers the physiological principles and clinical applications of heat and cold therapy in sports and provides information on how to use them for specific indications.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Cryotherapy; CWI; Muscle injuries; Muscle metabolism; PRICE; Sports injuries